The effect of occupational stress on depression and insomnia: a cross-sectional study among employees in a Ghanaian telecommunication company - Emma Edinam Kploanyi; Duah Dwomoh; Mawuli Dzodzomenyo (BMC, 2020)
Abstract Background Depression and insomnia are major psychiatric conditions predicted by occupational stress. However, the influence of occupational stress on these two conditions is under-explored in telecommunication companies, especially in Africa. This research was conducted to assess occupational stress in a Ghanaian telecommunication company and its effect on depression and insomnia. Methods An analytical cross-sectional study was conducted among employees at a telecommunication company in Accra. Structured self-administered questionnaires were used in collecting data from 235 respondents using simple random sampling. The Chi-square test of independence and Wilcoxon Rank-Sum test were employed to assess the significance of associations with subsequent sensitivity analysis using Multiple logistic, Poisson and Probit regression models. Occupational stress was matched on four variables: age of the workers, marital status, responsibility for dependents and work experience, to improve on the estimation of its impact on symptomatic depression and insomnia using the coarsened exact matching procedure. Results More males (52.8%) than females participated in this study. The age range for study participants was 20-49 years with a mean of 30.8 ± 6.9 years. The prevalence of excessive occupational stress reported by the employees was 32.8% (95% CI = 26.7-38.8). More than half of respondents (51%) reported depressive symptoms in the past week and only a few (6%) reported being diagnosed with insomnia in the past year. Age, responsibility for dependents and work experience were the only background characteristics that were significantly associated with excessive occupational stress. After controlling for background characteristics, the estimated risk of reporting symptoms of depression among employees who reported excessive stress from work was only 5% higher [ARR; 95% CI = 1.05 (0.94-1.17)] whereas it was 2.58 times the risk of reporting insomnia [ARR; 95% CI = 2.58(0.83-8.00)] compared to those who did not report excessive stress from their jobs. The relative risk reduced to 2.46[ARR; 95% CI = 2.46(0.77-7.87)] and 1.03[ARR; 95% CI = 1.03(0.91-1.17)] for insomnia and depression respectively after employing Poisson regression with CEM. Conclusion The study found a higher risk of insomnia among employees who reported excessive occupational stress compared to those who did not. However, this study did not find a statistically significant relationship between depression and occupational stress.